Effects of Low-Temperature Stress and Brassinolide Application on the Photosynthesis and Leaf Structure of Tung Tree Seedlings - Zhang, Fanhang; Lu, Kun; Gu, Yiyang; Zhang, Lin; Li, Wenying; Li, Ze (Frontiers in Plant Science, 2020)
Tung tree is an important woody oil tree species. Tung oil extracted from the tung fruit seeds is used in the manufacture of environmentally-friendly paint. This study investigated the effects of the application of brassinolide (BR) under different temperature conditions on the chlorophyll content, photosynthesis, chlorophyll fluorescence, leaf anatomical structure, and chloroplast ultrastructure in Vernicia fordii and Vernicia montana. The conditions used were 8°C-Control (low temperature and no BR), 8°C-BR (low temperature and BR application), 28°C-Control (normal temperature and no BR) and 28°C-BR (normal temperature and BR application), and effects were monitored from 5 to 15days after the treatments (DAT). The results showed that the low temperature treatment (8 °C-Control) significantly reduced the net photosynthetic rate (Pn), stomatal conductance (Gs), maximum fluorescence (Fm), maximum photochemical efficiency (Fv/Fm), and actual photochemical and quantum efficiency (ΦPSII) compared to the control condition (28°C-Control). However, the external application of BR alleviated the negative effects of low-temperature stress to some degree for all the above parameters for both species tested, except for Pn and Gs at 15 DAT. There were no significant differences in most of the parameters in either species between the 28°C-Control and 28°C-BR treatments. At 10 and 15 DAT of low-temperature stress, the 8°C-Control treatment significantly reduced leaf cell tense ratio (CTR) and increased spongy ratio (SR) compared to 28°C-Control, whereas BR application alleviated the adverse effects. Moreover, the 8°C-Control treatment significantly destroyed the chloroplast structure, loosening the thylakoids until they disintegrated, while exogenous spraying of BR protected the chloroplast structure and enabled it to function properly in both species. Our results suggested that long-term low temperatures significantly reduced the photosynthetic efficiency of tung tree seedlings, affecting the formation of the internal structure of plant leaves and destroying the integrity and function of the chloroplast. To prevent this, external application of BR to tung tree seedlings could enhance the photosynthetic potential of tung trees by maintaining the stability of the leaf structure, morphology, and function, and alleviating the damage caused by cold injury. The results also showed that V. fordii seedlings are more resistant to low temperatures than V. montana seedlings.